Water Quality Test of the River in the Campus Area of Universitas Negeri Padang in a Simple Way - Fristia, Yolla (Jurnal Serambi Biologi, 2023)
The UNP campus area is crossed by a river that flows from the Basko area to Muaro Gantiang Beach, and this river is known as the "Gangga" River at UNP. The river, which is located right in the Padang State University area, is surrounded by residential areas, so there are many household activities that are directly related to the river. However, the condition of the river when viewed from the surface does not show indications of a clean river, such as cloudy water color and quite pungent odor. Therefore, it is important to do early detection of pollution in order to prevent adverse impacts on the surrounding community. The methods used were observation and experimentation. Pollution detection procedures are carried out through two types of physical and chemical analysis. The test results showed that there were indications of pollution in the Ganges River through simple physical and chemical tests. The results also show that the Ganges River water cannot be used as a raw water source for drinking water needs.